Determinants of Young Catholics Participation in the Eucharist in the Diocese of Manado: An AHP and Fuzzy-AHP Analysis - Stenly Vianny Pondaag; Jozef Richard Raco; Yulius Christian Raton (Jurnal Ledalero, 2026)
Eucharistic participation among Catholic youth is increasingly influenced by complex, multi-dimensional motivations that cannot be accurately captured through conventional qualitative surveys. This study aims to quantify and hierarchically prioritize the fundamental factors motivating young Catholics in the Diocese of Manado to attend the Eucharistic celebration. This research employs a quantitative approach utilizing Operations Research models, specifically integrating the Analytic Hierarchy Process (AHP) and Fuzzy-AHP. Data were collected through purposive sampling from 147 active young Catholics (aged 15–35 years). The integration of Buckley’s Fuzzy-AHP method was utilized to mitigate linguistic ambiguity in spiritual perception and to ensure mathematical consistency in pairwise comparisons. The synthesis reveals that the belief in the "Real Presence of Christ" is the strongest empirically identified motivation for Eucharistic participation, surpassing institutional compliance, familial habits, and communal peer influence. These findings provide an evidence-based diagnostic framework for diocesan pastoral planning. Rather than focusing solely on communal social gatherings, youth catechesis programs must strategically pivot towards profound liturgical formation, as theological depth is the most critical factor sustaining long-term youth engagement in the Church.